Surgical and nonsurgical treatment of total rupture of the pectoralis major muscle in athletes: update and critical appraisal - Jörn Kircher; Christoph Ziskoven; Thilo Patzer; et al (Dove Medical Press, 2010)
Jörn Kircher, Christoph Ziskoven, Thilo Patzer, Daniela Zaps, Bernd Bittersohl, Rüdiger KrauspeUniversity Hospital, Orthopaedic Department, Heinrich-Heine University Düsseldorf, Düsseldorf, GermanyAbstract: The complete rupture of the pectoralis major tendon is an uncommon injury but has become increasingly common among athletes in recent years. This may be due to a higher number of individuals taking part in high-impact sports and weightlifting as well as the use of anabolic substances, which can make muscles and tendons vulnerable to injury. In recent literature, there are only few recommendations to rely on conservative treatment alone, but there are a number of reports and case series recommending early surgical intervention. Comparing the results of the two treatment regimens, there is clear evidence for a superior outcome after surgical repair with better cosmesis, better functional results, regaining of muscle power, and return to sports compared with the conservative treatment. In summary, anatomic surgical repair is the treatment of choice for complete acute ruptures of the pectoralis major tendon or muscle in athletes.Keywords: pectoralis major, rupture, athlete, conservative treatment, surgical treatment, steroid, tendon, sports injury